Design and Analysis of SIW Bandstop Filters for Interference Suppression in X Band - Mazlan, Mohammad Hanif; Ahmad, Badrul Hisham; Husain, Mohd Nor; Zakaria, Zahriladha; Shairi, Noor Azwan; Zahari, Mohd Khairy; Hassan, Nornikman (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
In this paper, six different bandstop filter designs using Substrate Integrated Waveguide (SIW) resonator coupled to microstrip transmission line is presented. A curved and rectangular SIW resonator was designed and then coupled to microstrip transmission line to provide a band reject response in Advanced Design System Momentum RF software. These filters were designed for interference suppression in X-band and simulated on Rogers RO4350 substrate with thickness of 0.508 mm and relative dielectric constant of 3.48. The simulated result was compared with other bandstop filter at X-band and showed a good suppression at 9 GHz region with attenuation of -61.9 dB and -3 dB bandwidth of 90 MHz.